2020
DOI: 10.1097/bot.0000000000001877
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Dislocation or the Modified Heuter Anterior Approach for Pipkin I and II Femoral Head Fracture Dislocations

Abstract: Objectives: To compare outcomes after surgical treatment of Pipkin I and II femoral head fractures treated with either a surgical dislocation (SD) or a direct anterior approach (the modified Heuter approach). Study Design: Retrospective, multicentre. Setting: Three Level I trauma care centers. Patients: Fourty-nine patients operated for Pipkin types I or II femor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although some studies have reported satisfactory results of nonsurgical treatment in patients with non-displaced Pipkin type I and type II fractures, this treatment has almost been abandoned because of the high rate of complications associated with longstanding patient immobility and the high cost of prolonged admission [ 1 , 6 9 ]. And more and more investigators recommend surgical treatment of femoral head fractures [ 1 3 , 8 , 10 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have reported satisfactory results of nonsurgical treatment in patients with non-displaced Pipkin type I and type II fractures, this treatment has almost been abandoned because of the high rate of complications associated with longstanding patient immobility and the high cost of prolonged admission [ 1 , 6 9 ]. And more and more investigators recommend surgical treatment of femoral head fractures [ 1 3 , 8 , 10 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the presence of avascular necrosis of the femoral head, associated complications in using screw xation can only be avoided and reduced by improving the surgical technique applied. Current surgical approaches for femoral head fractures vary and include the medial approach (Ludloff approach) and the anterior approach (Smith Petersen approach), the antero-medial fenestration approach, the Watson-Jones Approach, the lateral approach and the Kocher-Langenbeck approach [13][14][15][16]. Despite these options, it remains a challenge to easily expose the femoral head and complete the reduction and xation under direct vision.…”
Section: Introductionmentioning
confidence: 99%